The intellectual life of the British working classes - Rose, Jonathan, 1952- (Yale University Press, 2021)
This is a landmark intellectual history of Britain's working classes from the preindustrial era to the twentieth century. Drawing on workers' memoirs, social surveys, library registers, and more, Jonathan Rose uncovers which books people read, how they educated themselves, and what they knew. A new preface addresses the continuing relevance of the book amidst the upheavals of the present day. ""An astonishing book.""--Ian Sansom, The Guardian ""A passionate work of history. ... Rose has written a work of staggering ambition.""--Daniel Akst, Wall Street Journal Winner of the SHARP Book Histor